1977
DOI: 10.1007/bf00340017
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary abscess

Abstract: Three cases of pituitary abscess are presented. The history of recurrent attacks of aseptic meningitis, together with radiological and clinical features suggestive of pituitary tumor, appear to form a fairly typical picture of the condition. Long follow-up was possible in two of the cases. There are no radiological features which distinguish the lesion from pituitary tumor, hence the importance of recognizing the significance of such a clinical presentation with radiological evidence of sellar enlargement. Pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…4,7,12,14,17,19,23,24,26,28) Recently, magnetic resonance (MR) imaging has shown that pituitary lesions are quite common, but pituitary abscess is rare. Two cases of pituitary abscess were identified intraoperatively in a series of 500 pituitary expansive lesions, 26) and a series of six cases of pituitary abscess accounted for 0.6% of total pituitary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…4,7,12,14,17,19,23,24,26,28) Recently, magnetic resonance (MR) imaging has shown that pituitary lesions are quite common, but pituitary abscess is rare. Two cases of pituitary abscess were identified intraoperatively in a series of 500 pituitary expansive lesions, 26) and a series of six cases of pituitary abscess accounted for 0.6% of total pituitary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,18,29 Microscopic identification of massive polymorphonuclear leukocytes or macrophages with underlying necrosis leads to the diagnosis of pituitary abscess. 18 However, as these microscopic findings may mimic those of pituitary tumor infarction 12,26,30 or necrotizing infundibuloneurohypophysitis, 11 examination of the cyst wall and the surrounding pituitary gland is important for the precise diagnosis. 11,18 Since the invention of antibiotics, pituitary abscess has become a treatable disease.…”
Section: Discussionmentioning
confidence: 98%
“…In most reported series, the diagnosis of pituitary abscess is not suspected pre-operatively (Hammann, 1955;Domingue and Wilson, 1977;Rudwan, 1977); however, in Nelson et al (1983) series of three cases of pituitary abscess which arose in association with pituitary adenomas, the diagnosis was suspected on the basis of enhancement of the sella mass.…”
Section: Discussionmentioning
confidence: 99%
“…On clinical grounds, the presence of an intra sellar abscess may be suspected in those patients who are thought to have pituitary tumours and who present with septic meningitis, especially if more than one attack of meningitis has occurred (Lindholm et al, 1973;Rudwan, 1977).…”
Section: Discussionmentioning
confidence: 99%